RANCANG BANGUN KNOWLEDGE MANAGEMENT SYSTEM UNTUK MENINGKATKAN KINERJA PEGAWAI PADA KANTOR CAMAT MEDAN TEMBUNG - Sahfitri, Fachira Nur; Triase, Triase; Sibarani, Fathiya Hasyifah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Knowledge is very influential on the running of an agency. By utilizing knowledge, agencies can improve their performance. The Medan Tembung sub-district office is the center of administration and public services at the sub-district level. The knowledge possessed by employees is currently not well documented because there is media that can store all the knowledge possessed by employees and the process of employee interaction in sharing their respective knowledge is carried out directly. This research aims to design and develop a system that can store all the knowledge possessed by general employees so that employee knowledge increases and employee performance increases. For this reason, a web-based knowledge management system was built, equipped with features such as departments, articles, comments, discussion attachments, users and activities. With the existence of a web-based knowledge management system, Medan Tembung sub-district office employees can successfully store, manage and share the knowledge that each employee has, thereby reducing the loss of knowledge that employees have due to transfer or retirement. Keyword: Knowledge, Knowledge Management System, Employees, General Department Abstrak: Knowledge sangat berpengaruh pada berlangsungnya suatu instansi. Dengan memanfaatkan pengetahuan, instansi dapat meningkatkan kinerjanya. Kantor camat medan tembung merupakan pusat administrasi dan pelayanan publik tingkat kecamatan. Pengetahuan yang dimiliki pegawai saat ini belum terdokumentasi dengan baik dikarenakan belum adanya media yang dapat menyimpan semua knowledge yang dimiliki pegawai dan proses interaksi pegawai dalam sharing knowledge masing dilakukan secara langsung. Penelitian ini memiliki tujuan yaitu untuk merancang dan mengembangkan sistem yang bisa menyimpan semua pengetahuan yang dimiliki pegawai bagian umum sehingga knowledge pegawai bertambah dan kinerja pegawai menjadi meningkat. Untuk itu dibangunlah sebuah sistem knowledge management system berbasis web dengan dilengkapi fitur – fitur seperti departemen, artikel, komentar, lampiran diskusi, pengguna dan aktivitas. Dengan adanya sistem knowledge management system berbasis web, pegawai kantor camat medan tembung dapat berhasil menyimpan, mengelola dan membagikan knowledge yang dimiliki setiap pegawai sehingga mengurangi kehilangan pengetahuan (knowledge) yang dimiliki pegawai karena mutasi atau pensiun. Kata kunci: Knowledge, Knowledge Management System, Pegawai, Bagian Umum